Clinical research : from proposal to implementation - McPhaul, Michael J.; Toto, Robert D.; Lee, Simon J. Craddock; Sadler, John Z. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Clinical and translational research is a crucial link to the improvement of clinical care and practice. Many of the elements that are involved--physicians, nurses, pharmacists, laboratory testing, medical records--are also involved in the delivery of care to patients. Yet in the conduct of clinical research, these elements are arrayed in different configurations and constrained by rules and regulations that are distinct from those that guide the practice of medicine. In parallel with these considerations, the conduct of clinical research demands a specific skill set. Specialized tools are required to formulate and design informative clinical trials and to interpret the findings from such experiments"--Provided by publisher.
(Publisher-supplied data) Chapter 1 Assembling and Organizing a Research Team / Robert D. Toto -- Chapter 2 Institutional Review Board Approval / Suzanne M. Rivera -- Chapter 3 Writing Informed Consent Documents and Obtaining Informed Consent / Anne Clark, Suzanne M. Rivera, Diane Sheppard, Darren K. McGuire, and Michael J. McPhaul -- Chapter 4 Ethics of Data Sharing and the Handling of Genetic Information / Richard Scheuermann and Bradley Malin -- Chapter 5 Writing a Statistical Analysis Plan Beverley Adams-Huet and Chul Ahn -- Chapter 6 Protocol Implementation Procedures / Tammy L. Lightfoot -- Chapter 7 Screening and Evaluation / Robert D. Toto -- Chapter 8 Recruitment and Retention / Tammy L. Lightfoot -- Chapter 9 How to Set Up Your Database / Janet Smith -- Chapter 10 Budgeting Process and Management / Deanna S. Adams -- Chapter 11 Implementation of Investigational Drug Studies / M.E. Blair Holbein -- Chapter 12 Collecting Data / Deanna S. Adams -- Chapter 13 Data and Safety Monitoring / Andrea M. Nassen -- Chapter 14 Presenting, Writing, and Publishing Challenges / Charles T. Quinn and A. John Rush.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Clinical trials; Electronic books